Juggling - Sinclair, Stewart Lawrence (Book collections on Project MUSE., 2023)
Stewart Sinclair explores the 4,000 year history, culture, and practice of juggling as seen through his life as a juggler, showing how it provides joy as well as a respite from difficulties during hard times.